Impact if VAT regimes on organisation of producers' operations under CAP financial instruments for the fruit and vegetable sector - Server Izquierdo, R.J.=700 1 Marin Sanchez, M.M.
(Es, En)
ilus., 20 ref.
Keywords: FINANCIAMIENTO; COMUNIDADES RURALES; CONTABILIDAD; TRIBUTACION INDIRECTA; ESPAÑA; FONDOS OPERATIVOS; NEUTRALIDAD